How not to get sick : a cookbook and guide to prevent and reverse insulin resistance, lose weight, and fight chronic disease - Bikman, Benjamin, 1977-; Keuilian, Diana, 1981- (BenBella Books, Inc., 2024)
"In this companion guide to Why We Get Sick and featuring 70 low-carb and keto-friendly recipes, Bikman has teamed up with the fitness expert and recipe developer Diana Keuilian to help the nearly 9 in 10 American adults affected with insulin resistance. Together, they translate the latest research into actionable, easy-to-follow steps"--